2017
DOI: 10.1248/bpb.b17-00112
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Histamine-Forming Enzyme Histidine Decarboxylase in Skeletal Muscles by Prolonged Muscular Work: Histological Demonstration and Mediation by Cytokines

Abstract: Recent studies suggest that histamine-a regulator of the microcirculation-may play important roles in exercise. We have shown that the histamine-forming enzyme histidine decarboxylase (HDC) is induced in skeletal muscles by prolonged muscular work (PMW). However, histological analysis of such HDC induction is lacking due to appropriate anti-HDC antibodies being unavailable. We also showed that the inflammatory cytokines interleukin (IL)-1 and tumor necrosis factor (TNF)-α can induce HDC, and that PMW increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Histamine plays also an important role as a regulator of microcirculation in muscles during exercise and sustained post-exercise vasodilation [51,52]. Histidine decarboxylase expression is induced in mast cells, vascular endothelial cells, and muscle fibers themselves by cytokines (particularly IL-1 and TNF-α), increased temperature, decreased pH, and hypoxia-inducible factor 1 [53][54][55][56].…”
Section: Histaminementioning
confidence: 99%
“…Histamine plays also an important role as a regulator of microcirculation in muscles during exercise and sustained post-exercise vasodilation [51,52]. Histidine decarboxylase expression is induced in mast cells, vascular endothelial cells, and muscle fibers themselves by cytokines (particularly IL-1 and TNF-α), increased temperature, decreased pH, and hypoxia-inducible factor 1 [53][54][55][56].…”
Section: Histaminementioning
confidence: 99%
“…In addition, our data suggested that bone marrow–derived HDC‐expressing CD11b + immune cells cannot be induced to transform into skeletal muscle or myoblasts. A recent study reported that prolonged muscular work (PMW) induces HDC expression in the endomysium and around blood vessels and some muscle fibres, using anti‐HDC IHC staining . PMW requires a large supply of O 2 and induces hypoxia in the tissue, which might cause slight inflammation in skeletal muscle and further recruit HDC‐expressing CD11b + myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…In resting skeletal muscle, HDC enzyme activity generates minute quantities of histamine (7). HDC mRNA expression, protein abundance, and activity are increased with exercise (1,2). HDC activity appears to be enhanced by increased temperature (7,8), decreased pH (8), hypoxia (6), and several signaling molecules such as interleukin-1 (2,9), all of which may play a role during repeated muscle contractions.…”
Section: Histamine In Exercise Responsesmentioning
confidence: 99%
“…Skeletal muscle interstitial histamine concentrations are low at rest, but increase in active musculature during moderate-intensity endurance exercise (1). Histamine is released by mast cell degranulation and produced through de novo synthesis (1), secondary to increased activity of the enzyme histidine decarboxylase (HDC) (1,2). Mast cell degranulation has been shown to occur with stimuli associated with exercise such as hypoxia, increased temperature, vibration, and hyperosmolality (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation